What are the benefits of the Portuguese public investment projects? - Teixeira, C. (2015)
The aim of this paper is to provide a deeper understanding about the effective benefits of public investment projects carried out in Portugal, since their entry into the European Union, in 1986, so far and, additionally, to know the main causes for cost Project deviations. Since the entry of Portugal in European Union, the country image has changed, where public investment in infrastructure played a critical role. However one question remains unanswered which are frequently asked by Portuguese people, namely: • What are the Benefits of the Portuguese Public Investment Projects? In addition to the above question, the present study will try as well to answer the following question: • What were the main causes for the project deviations? This research allowed conclude that, although cost/investment deviations have been observed in the majority of projects, and reported through public audits, the benefits deviation analysis between the estimated values to society and what their realization was, are in the most cases, unknown. Portuguese national authorities are concerned to measure the deviation of costs/investment, but nobody has analyzed so far the benefits deviation for society and community.